Effect of plasma surface modification on pullout characteristics of carbon fiber-reinforced cement composites. (April 2021) - Kim, Jin Hee; Han, Jong Hun; Hong, Seungki; Kim, Doo-Won; Park, Sang Hee; Wee, Jae-Hyung; Yang, Kap Seung; Kim, Yoong Ahm
Highlights: The surface of the unsized pristine carbon fibers was activated via three plasma treatments Plasma treatments are effective to remove the coated sizing agent Plasma treatments introduced hydrophilic functional groups and increased surface roughness Carbon fiber bundles were pulled out from a cementitious matrix The argon plasma-treated carbon fibers exhibited the highest interfacial shear strength Abstract: Light but strong carbon fibers have been utilized as effective reinforcing lattices for cement matrices. However, to explore the intrinsic properties of carbon fibers within the cement matrix, the interfacial behavior between the fiber and matrix must be understood in terms of the bond strength as well as the interfacial failure mode. In the present work, we evaluated the pullout properties of carbon fiber bundles from a cementitious matrix after the fibers were modified via one of three plasma treatments using argon, nitrogen, or oxygen. The plasma-treated carbon fibers were characterized using Raman spectroscopy, X-ray photoelectron spectroscopy, and scanning tunneling microscopy. The treatments introduced hydrophilic functional groups on the carbon fibers' surfaces and increased their surface roughness. With an appropriate amount of hydrophilic groups on the carbon fiber surface, the rate of hydration was accelerated, which led to a denser cement structure surrounding the carbon fibers. In addition, the fibers' surface roughness was critical toward improving mechanical interlocking between the fibers and cement matrix. The highest interfacial shear strength for the argon plasma-treated sample can be explained by the improvement in surface roughness without degrading the mechanical strength of the carbon fiber, as well as the modification of the surface from hydrophobic to hydrophilic. Graphical Abstract: Image, graphical abstract